SCOPE AND CAREER OPPORTUNITIES THROUGH PHYSICS - Mody, A. K. (SCHOOL SCIENCE, 2011)
This article discusses what Physics encompasses as a subject upto Intermediate level and application of it can lead to as one pursue the same beyond +2 level. It also touches upon career opportunities available to Physics graduates. The purpose of the article is to illustrate for students of +2 Science stream and physics undergraduate students, possible opportunities which physics offers as a discipline and also to motivate undergraduate physics students who may otherwise be pursuing graduation in absence of any (so called) better opportunity, just for sake of graduation, a most likely contemporary scenario.